(untitled) (Contemporary Journal of Social Science Review, 2024)
The study explores Farrukhi’s The Itch through an existentialist lens, emphasizing the protagonist’s search for meaning and the portrayal of the human condition. The study explores the protagonist’s existential crisis through the symbol of the itch, reflecting the broader human search for meaning and purpose. Grounded in Sartre’s existentialist theory, which emphasizes individual freedom and the creation of personal meaning, the research examines how the protagonist’s experiences and choices shape his understanding of himself and the world around him. The study adopts a qualitative methodology, analyzing the narrative structure and symbolic elements of the text to uncover how the itch functions as a metaphor for the protagonist’s internal struggle with the lack of inherent meaning in life. By applying Sartre’s concept of "existence precedes essence," the research highlights how the protagonist’s search for meaning arises from his confrontation with an indifferent world, leading to both existential anxiety and moments of self-creation. The findings suggest that the itch symbolizes the persistent, unresolved desire for purpose in the face of existential freedom.